Optimization of Process Parameters and effect of Vegetable Powder Incorporation on Physical Quality Attributes of Pearl Millet Extrudates - srivastava, Soma; Jain, Dilip (Annals of Arid Zone, 2025)
This study examined the extrusion cooking of pearl millet and maize blends, focusing changes in physical properties and the effects of incorporating spinach and beetroot powders. Single screw extruder powered by 5.0 kW motor and a rotational speed of 1450 rpm was used to produce extrudates. Pearl millet and maize grits having 13% moisture content and mixed in the ratio of 70:30, 50:50, and 30:70 on weight basis were used for extrusion. The study adopted simplex-lattice mixture design and augmented mixture design for blend formulations. The effect of blend proportions was studied on physical properties of extrudates such as expansion ratio, bulk density, volume mass anddiameter. Extrudates expansion ratio decreased with higher pearl millet proportions, while maize improved expansion ratio. The expansion ratio was highest for 100% maize (4.64), decreasing with pearl millet addition. Spinach and beetroot powders mixed in the range of 1- 4% also reduced expansion and increased bulk density, attributed to fibre content which disrupt starch gelatinization. Optimal powder levels (3%) resulted in desirable physical properties. Bulk density peakedat 0.057 g cm-³ and 0.071 g cm-³ for spinach and beetroot powders, respectively, at 4%. Findings highlighted trade-offs between density and expansion when incorporating vegetablepowders into extruded products. The study underscores the potential of optimized formulations for nutritious, shelf-stable, and texturally appealing snacks, addressing health-conscious consumer demands while ensuring product quality.